How Significantly to Emerging Economies Benefit From Board Attributes and Risk Management in Enhancing Firm Profitability? Seberapa Signifikan Keuntungan Ekonomi Berkembang Dari Atribut Dewan dan Manajemen Risiko dalam Meningkatkan Profitabilitas Perusahaan? - Tariq Tawfeeq Yousif Alabdullah; Essia Ries Ahmed; Mohammed Almashhadani; Sara Kadhim Yousif; Hasan Ahmed Almashhadani; Raghad Almashhadani; Eskasari Putri (Universitas Muhammadiyah Sidoarjo, 2021)
Recently, the literature review represented by its previous studies have witnessed obvious development that has been become the reason to create different trends. This paper aims to considerably contribute to the area of corporate governance to be then involved in the new trends testing the role of board attributes as mechanisms of corporate governance to know whether non-financial companies in the developing economies will benefit from these mechanisms in their impact of firm profitability. Thus, the present study tested 100 non-financial companies based on their annual reports in the year of 2020 as a cross sectional study. The results of testing the variables of the current study revealed that there is a negative link between board of directors size and profitability. On the other hand, the results showed that the managers independency has no relationship with profitability. Likewise, the results revealed that risk management has no effect on profitability. This study probably could be considered as a unique study due to its new contribution that fills the gap of what have been done in the previous studies in the area of corporate governance (CG) and profitability because it tested the link between risk management and growth. Hence, according to the researchers’ knowledge, there is no research that has been dealt with the two variables that were dealt by the current study. The current study introduces evidence to many parties, such as shareholders, scholar, executives and policy makers.